ヒガシ ナンキョク リュツォ・ホルムワン オングル カイキョウ ノ チジキ タンサ - 脇野, 定則; ワキノ, サダノリ; 船木, 實; フナキ, ミノル; 野木, 義史; ノギ, ヨシフミ; Wakino, Sadanori; Funaki, Minoru; Nogi, Yoshifumi (2001)
P(論文) 第35次南極地域観測において, 東南極, リュツォ・ホルム湾, オングル海峡で地磁気全磁力測定を行った。オングル海峡では, 南北および北北西-南南東走行の地磁気異常が観測された。オングル海峡の南西部以外では, 負の地磁気異常が卓越する。また, 地磁気異常は, 約-100nTから80nTの間で変化している。 Measurements of total intensity of the geomagnetic field were carried out during the 35th Japanese Antarctic Research Expedition (JARE-35) in Ongul Strait, Lutzow-Holm Bay, East Antarctica. N-S and NNW-SSE striking magnetic anomalies are observed in Ongul Strait. Negative magnetic anomalies are dominant except for the southwestern part of Ongul Strait. Magnetic anomalies vary from about-100nT to 80nT. departmental bulletin paper